2021
DOI: 10.1111/tpj.15375
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal allopolyploid grasses (Festuca × Lolium) display stable patterns of genome dominance

Abstract: Summary Allopolyploidization entailing the merger of two distinct genomes in a single hybrid organism, is an important process in plant evolution and a valuable tool in breeding programs. Newly established hybrids often experience massive genomic perturbations, including karyotype reshuffling and gene expression modifications. These phenomena may be asymmetric with respect to the two progenitors, with one of the parental genomes being “dominant.” Such “genome dominance” can manifest in several ways, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 80 publications
4
23
0
Order By: Relevance
“…S2). Based on species‐specific k‐mers derived from the previous study (Glombik et al ., 2021), we were able to analyze the parental allele‐specific expression for 15 kinetochore genes. Out of these, 13 genes did not show significantly different expression between homoeologues; however, two genes ( NDC80 and NNF1 ) were expressed exclusively from a Lolium homoeologue in all nine samples of the three pollen development stages and three biological replicates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2). Based on species‐specific k‐mers derived from the previous study (Glombik et al ., 2021), we were able to analyze the parental allele‐specific expression for 15 kinetochore genes. Out of these, 13 genes did not show significantly different expression between homoeologues; however, two genes ( NDC80 and NNF1 ) were expressed exclusively from a Lolium homoeologue in all nine samples of the three pollen development stages and three biological replicates.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we revealed that Festuca × Lolium hybrids used in this study displayed overall gene expression more frequently at the level of the Lolium parent; however, this was accomplished by overexpression of the Festuca allele. The study suggested that it is more likely that transcription factors from Lolium can manipulate the expression of Festuca alleles rather than transcription factors from Festuca modulating the expression of Lolium alleles (Glombik et al ., 2021). A study on a synthetic allopolyploid cotton revealed that the parental‐specific gene expression could be at least partially altered by developmental, environmental, and ecological conditions, such as during abiotic stress, even though the genome dominance seems to be deterministic (Dong & Adams, 2011; Glombik et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most, if not all, allopolyploids retain the expression level of one (dominant) parent (so-called expression level dominance) and/or display a preferential expression from the alleles of the dominant genome (so-called homoeolog expression bias). Such dominance does not involve all the expressed genes, as some genes can be overexpressed from the submissive genome or display the overall expression at the level of the submissive parent ( Edger et al, 2017 ; Bird et al, 2018 ; Glombik et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, genomic instability is often reported and a shift to the ryegrass genome over generations can happen in crosses with fescues (Kopecky et al 2017;Akiyama et al 2012). Additionally, homeolog expression bias and expression level dominance can be observed in such allopolyploids (Glombik et al 2021). Collectively, these phenomena may lead to distinct interactomes when hybridizations are performed across species, which can be analyzed through network reconstruction by leveraging high throughput omics data and appropriate statistical methods.…”
Section: Introductionmentioning
confidence: 99%